THE EFFECT OF GREEN COMPETITIVE ADVANTAGE AND SUPPLY CHAIN MANAGEMENT ON COMPANY PERFORMANCE WITH GREEN HUMAN CAPITAL AS A MODERATING VARIABLE - Diah Nurdiana (International Journal of Contemporary Accounting, 2022)
This research aims to determine whether there is an impact of green competitive advantage in supply chain management with green human capital as the moderating variable on company performance. In this study, the dependent variable used is company performance (Y), the independent variables are green competitive advantage and supply management (X), and the moderating variable is green human capital. Is this study, a non-probability sampling method was used. 50 textile companies in Jakarta were gathered as sample using non-probability sampling. Primary data was colleted by distributing closed questionnaires. The results of the study be seen through the determination coefficient of Ta given in Table Ta. The R-Square value of the company performance variable is 0.919, which shows that the dependent variable (Company Performance) can be explained by 91.9% of the independent variables (Green Competitive Advantage, Supply Chain Management, Green Human Capital) while the remaining 8.1% cannot be explained.